Cognitive decline gap between male and female in Indian context: Examining the contribution of underlying factors using non-linear decomposition analysis - Subhadeep Saha; Priya Das; Tanu Das; Partha Das; Tamal Basu Roy (Archives of Gerontology and Geriatrics Plus)
Background: Cognitive decline denotes the condition of having memory loss, reduced or slower thinking skills. It is an alarming issue with the increasing age of individuals and sometimes it hinders the smooth functioning of daily activities in life. Affirmations from both developed and developing countries manifest that older people are at risk of cognitive decline; however, the study about male-female differential remained scanty. So, the study examines gender-specific differences in cognitive decline among middle-aged and older adults by identifying the significant covariates responsible for the change in cognitive decline through the FDA. Methods: The study used information collected from 52,569 participants (females 26,665 and males 25,904) aged 45 years and above from the latest cross-sectional dataset of LASI. Descriptive statistics, multivariable logistic regression, and FDA techniques were utilized. Results: Multivariable logistic regression revealed that female individuals had 1.90 times [95% CI: (1.77-2.05)] higher odds of cognitive decline than male individuals. In addition, the FDA revealed that school attainment alone was found enough to narrate the difference in the pervasiveness of cognitive decline among individuals between males and females by 54.75%. Marital status, working status, and reading habits were found to express a profound impact on the male-female gap in the prevalence of cognitive decline by 9.41%, 6.47%, and 12.25% respectively. Conclusions: Findings suggest that there is a need for comprehensive public service intervention like community healthcare and formulation of various health programs to address the cognitive decline, more so for female individuals without neglecting the male ones.